Patient Satisfaction and Associated Factors During COVID-19 Pandemic in North Shoa Health Care Facilities - Deriba, Berhanu Senbeta (Patient Prefer Adherence, 2020)
BACKGROUND: Patient satisfaction is an indicator of healthcare quality service and involved as an outcome measure. Quality of healthcare service and patient satisfaction has been affected by the current coronavirus disease 2019 (COVID-19) pandemic. It induced uncertainness and shortage of medical supplies due to a limited global movement. Therefore, this study aimed to assess patient satisfaction and associated factors among chronic patients who had a follow-up in North Shoa healthcare facilities. METHODS: An institutional-based cross-sectional study was used to select 410 study participants through a systematic random sampling technique. Data were collected by a structured interviewer-administered questionnaire, entered into Epi Info version 7, and transported to SPSS version 23 for analysis. Bivariable and multivariable logistic regressions were used to identify the factors associated with satisfaction. The odds ratio with a 95% confidence interval was computed, and p-value <0.05 was considered statistical significance in the multivariable model. RESULTS: The overall level of patient satisfaction was 44.6%. The presence of sign and direction indicators (AOR=3.26, 95% CI=1.1, 9.92), obtaining some ordered drugs (AOR=3.7, 95% CI=1.1, 12.54), getting alcohol for hand cleaning (AOR=2.66, 95% CI=1.1,6.65), obtaining sanitizer for hand cleaning (AOR=4.45, 95% CI=1.72,11.52), and maintaining social distancing (AOR=2.63, 95% CI=1.21, 5.70) were factors associated with patient’s satisfaction. CONCLUSION: The level of patient satisfaction was very low during a COVID-19 pandemic. The presence of sign and direction indicators, availability of drugs, social distancing, availability of alcohol, and sanitizer were factors associated with patient satisfaction. The intervention targeted at increasing patient satisfaction and improving the quality of service during COVID-19 through maintaining social distancing and availing alcohol or sanitizers is necessary.